The Analyze by Finite Element of Strains in Periodontal Ligament and Alveolar Bone During Orthodontic Tooth Movement - Ionuț Luchian; Oana Țănculescu; Ioana Rudnic; Monica Tatarciuc; Silvia Mârţu (Romanian Journal of Oral Rehabilitation, 2012)
Orthodontic tooth movement (OTM) is achieved by applying an orthodontic force system to the brackets. The (re)modeling processes of the alveolar support structures are triggered by alterations in the stress ⁄ strain distribution in the periodontium. The aim of the present investigation was therefore to use the FEM, for to determine the influence of force magnitude in the stress and strain distribution in the alveolar support structures. Human jaws segments obtained from autopsy were micro CT-scanned and sample-specific finite element (FE) models were generated. The material behaviour of the PDL was considered to be nonlinear and non-symmetric and the alveolar bone was modeled according to its actual morphology. A series of Fe-analyses investigated the influence of the moment-to-force ratio, force magnitude, and chewing forces on the stress ⁄ strain in the alveolar support structures and OTM. Stress ⁄ strain findings were dependent on alveolar bone’s morphology. Because of the nonlinear behaviour of the PDL, distinct areas of tension, and compression could not be detected. Secondary load transfer mechanisms were activated and the stress ⁄ strain distribution in the periodontium was concealed by occlusal forces. The finite element method (FEM) has proved to be a valid and reliable technique for the calculation of the local state of deformation and loading of complex structures. Because roots and alveolar bone morphology are patient specific, FE-analysis of orthodontic loading regime should not be based on general models.